A Medical Training Game Using a Computer as a Teaching Aid - Kirsch, A. D. (Methods of Information in Medicine, 1963)
The Datatrol Corporation has developed a model for a computerized medical training game to be used as a teaching aid. This training game will utilize a computer capable of generating, from probability tables, synthetic patients who will exhibit symptoms guaranteed possible with an accuracy probability plus or minus a fixed percent. The symptoms of these synthetically generated patients will be presented to medical personnel and / or students for diagnosis. Approximately ten students may play the game simultaneously, each following their individual line of diagnosis. They will be allowed, if they desire, to request past historical data and to conduct laboratory tests and have synthetic results generated. As mentioned in the body of the paper, outside assistance will be sought for the preparation of various tables of probabilities needed for the game. The game is visualized as providing a contribution to medical education that could be used in conjunction with student medical meetings, professional meetings, or a tour of medical school centers. In order to allow this game to be used on the various standard computers that might be available at different medical schools or medical centers, the programs will be written in a generalized computer language such as FORTRAN. Possible fringe benefits of this game would be its use as an experimental research tool.Die Datatrol Corporation hat ein Modell für ein maschinelles medizinisches Diagnosetraining entwickelt, das als Lehrmittel im Rahmen der ärztlichen Ausbildung eingesetzt werden kann. Dabei wird ein Computer benutzt, der imstande ist, mit Hilfe von Wahrscheinlichkeitstabellen ,,synthetische Patienten” zu simulieren, deren dargebotene Symptomatik mit einem festzulegenden Genauigkeitsgrad möglich ist. Die Symptome dieser synthetischen Patienten werden ärztlichem Personal bzw. Studierenden zur Diagnose vorgelegt werden. Etwa zehn Teilnehmer können gleichzeitig üben, wobei jeder bis zur Stellung der Diagnose individuell vorgehen kann. Den Teilnehmern ist es gestattet, nach Wunsch früher erhobene Befunde heranzuziehen, Laboratoriumsuntersuchungen anzustellen und die Ergebhisse schrittweise zu synthetisieren. Für die Aufstellung der benötigten Wahrscheinlichkeitstabellen sollen geeignete Stellen zur Mitwirkung gewonnen werden. Das Verfahren ist als Beitrag zur medizinischen Ausbildung gedacht und kann in Verbindung mit Studienkursen, Fortbildungskursen oder im Lehrplan medizinischer Hochschulen Anwendung finden. Damit das Lehrspiel auch auf den verschiedenartigen, den einzelnen Hochschulen etwa verfügbaren Standardcomputern gespielt werden kann, werden die Programme in einer allgemein verbreiteten. Maschinensprache, wie z. B. FORTRAN, geschrieben werden. Ein weiterer möglicher Nutzen des Verfahrens könnte sein Einsatz als experimentelles Forschungsinstrument sein.